Estratégias de motivação no treinamento de força - Sponga, Alessander Angelo (My University, 2020)
With the increase in the number of students in the academies and the greater search for Strength Training (TF), it has become increasingly important to understand the reasons that lead to practice the sport and the factors that make them feel motivated. Knowing these aspects we will be able to direct to what extent the motivation will be decisive for the student's permanence in this type of training and how we can achieve them. Motivation is the major component in regular physical exercise, the main factor for the student to stay focused and stay faithful to classes, how important the role of the Physical Education professional / Trainer is for the student stay frequent and feel motivated in practice. Objective: To identify the impacts generated in the regular practice of Strength Training from the use of motivation strategies in gyms in the city of Flores da Cunha - RS. Materials and Methods: Quantitative, descriptive and exploratory research with a transversal bias. The sample, for convenience, consisted of 67 individuals, 36 males and 31 females, aged between 18 and 70 years, attending gymnasiums in the city of Flores da Cunha, located in the state of Rio Grande do Sul. The instrument used was a closed, self-administered questionnaire containing 12 questions. For the statistical treatment, the IBM ® SSPS Statistics 21.0 software and the Microsoft Excel program were used, where descriptive measures (means, standard deviation, frequencies and percentages) were calculated. Results: Through data analysis, it was found out of the 67 research participants, (32.5%) seek quality of life in the practice of TF, (32.5%) claim that the monitoring of the Physical Education professional (EFI) motivates you to stay in the sport. In relation to the total number of participants (21.6%), they have already abandoned the practice due to an injury or surgery, (32.4%) affirms that the change in the structure of the gym can be decisive for motivation. Already (61.2%) affirms that the results obtained with TF motivate a lot and (70.14%) feel motivated with a closer monitoring by the EFI professional. Final considerations: With the data collected you can conclude that motivation occurs in two ways, intrinsic and extrinsic according to the Theory of Self-Determination (TAD) and both are important to keep the student focused on the modality. In the female sex, the search for TF happens more for quality of life, in the male, it happens due to aesthetics, and that the monitoring of EFI professionals and the structure of the academy are crucial to keep students motivated. [resumo fornecido pelo autor]
Com o crescimento do número de alunos nas academias e a maior busca pelo Treinamento de Força (TF), tornou-se cada vez mais importante entender os motivos que leva a praticar a modalidade e os fatores que fazem os mesmos se sentirem motivados. Sabendo desses aspectos conseguiremos direcionar a que ponto a motivação vai ser determinante para a permanência do aluno nesse tipo de treinamento e como podemos atingi-los. A motivação é o grande componente na prática regular de exercícios físicos, o principal fator para que o aluno se mantenha focado e que permaneça fiel às aulas, o quão importante é o papel do profissional de Educação Física/Treinador (a) para que o aluno permaneça frequente e se sentindo motivado na prática. Objetivo: Identificar os impactos gerados na prática regular do Treinamento de Força a partir do uso de estratégias de motivação nas academias da cidade de Flores da Cunha - RS. Materiais e Métodos: Pesquisa quantitativa, descritiva e exploratória com viés transversal. A amostra, por conveniência, contou com 67 indivíduos, sendo 36 do sexo masculino e 31 do sexo feminino, com idade entre 18 a 70 anos, frequentadores de academias da cidade de Flores da Cunha, localizadas no estado do Rio Grande do Sul. O instrumento utilizado foi um questionário fechado, autoaplicável e contendo 12 questões. Para o tratamento estatístico, foi utilizado o software IBM ® SSPS Statistics 21.0 e o programa Microsoft Excel onde foram calculadas medidas descritivas (médias, desvio padrão, frequências e porcentagens). Resultados: Através da análise de dados, foi constatado dos 67 participantes da pesquisa, (32,5%) buscam qualidade de vida na pratica do TF, (32,5%) alegam que o acompanhamento do profissional de Educação Física (EFI) os motiva para se manter na modalidade. Em relação ao total dos participantes (21,6%) já abandonaram a prática devido alguma lesão ou cirurgia, (32,4%) afirma que a mudança na estrutura da academia pode ser determinante para a motivação. Já (61,2%) afirma que os resultados obtidos com o TF motivam bastante e (70,14%) sente-se motivado com um acompanhamento mais próximo do profissional de EFI. Considerações finais: Com os dados coletados podemos concluir que a motivação ocorre de duas formas intrínseca e extrínseca segundo a Teoria da Autodeterminação (TAD) e, ambas são importantes para manter o aluno focado na modalidade. No sexo feminino a busca pelo TF acontece mais pela qualidade de vida, já no masculino acontece devido a estética e, percebemos também que o acompanhamento dos profissionais de EFI e a estrutura da academia são determinantes para manter os alunos motivados. [resumo fornecido pelo autor]
Keywords: Exercícios físicos; Musculação; Motivação (Psicologia)